Exosomes from neuronal stem cells may protect the heart from ischaemia/reperfusion injury via JAK1/2 and gp130. Issue 9 (1st April 2021) - Katsur, Miroslava; He, Zhenhe; Vinokur, Vladimir; Corteling, Randolph; Yellon, Derek M; Davidson, Sean M
Abstract: Myocardial infarction requires urgent reperfusion to salvage viable heart tissue. However, reperfusion increases infarct size further by promoting mitochondrial damage in cardiomyocytes. Exosomes from a wide range of different cell sources have been shown to activate cardioprotective pathways in cardiomyocytes, thereby reducing infarct size. Yet, it is currently challenging to obtain highly pure exosomes in quantities enough for clinical studies. To overcome this problem, we used exosomes isolated from CTX0E03 neuronal stem cells, which are genetically stable, conditionally inducible and can be produced on an industrial scale. However, it is unknown whether exosomes from neuronal stem cells may reduce cardiac ischaemia/reperfusion injury. In this study, we demonstrate that exosomes from differentiating CTX0E03 cells can reduce infarct size in mice. In an in vitro assay, these exosomes delayed cardiomyocyte mitochondrial permeability transition pore opening, which is responsible for cardiomyocyte death after reperfusion. The mechanism of MPTP inhibition was via gp130 signalling and the downstream JAK/STAT pathway. Our results support previous findings that exosomes from non‐cardiomyocyte‐related cells produce exosomes capable of protecting cardiomyocytes from myocardial infarction. We anticipate our findings may encourage scientists to use exosomes obtained from reproducible clinical‐grade stocks of cells for their ischaemia/reperfusion studies.